Prinsip Manajemen Risiko Dalam Surah Al-Kahfi Ayat 60 - 82 - Hilyati Inayah Siregar (ITB AAS INDONESIA Surakarta, 2023)
This study aims to examine the relevance of the story of Prophet Musa AS learning to Khidr in surah Al-Kahf verses 60-82, associated with risk management theory. This descriptive analysis research uses literature sources from the book of interpretation, the book of qawaid fiqh and risk management. Through content analysis, this research concludes that Khidr's actions of destroying a boat, killing a small child and rebuilding a wall that almost collapsed are one of the stages of risk management, namely the response of choosing to take a smaller risk of loss to avoid a larger loss. Risk management is in line with the rule of fiqh